2008
DOI: 10.1007/s11243-008-9131-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interactions of a novel ruthenium(II) complex with G-quadruplex DNA

Abstract: A novel ruthenium(II) porphyrin complex, [Ru(phen) 2 MPyTPP] (phen = phenanthroline, MPyTPP = mono-(3 0 -Pyridine)-10,15,20-triphenyl porphyrin), has been prepared and characterized by elemental analysis, ESI-MS and NMR methods. The interaction of the complex with G-quadruplex DNA has been studied by spectroscopy, and the results have shown that [Ru(phen) 2 MPyTPP] can bind to G-quadruplex d(TTAGGG) 4 with high affinity. In the presence of d(TTAGGG) 4 , the characteristic Soret and intra-ligand (IL) transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…In einer solchen Verbindung (Abbildung 15 a) wurde ein Pyridinligand mit einem Porphyrinring verknüpft,45 um die Lipophilie und damit die Bioverfügbarkeit zu erhöhen. Dieser Komplex bindet mit so hoher Affinität an den H‐Telo‐Quadruplex, dass dessen Parallelkonformation zerstört wird.…”
Section: Verbindungen Die Mit Dna üBer π‐Stapelung Wechselwirkenunclassified
See 1 more Smart Citation
“…In einer solchen Verbindung (Abbildung 15 a) wurde ein Pyridinligand mit einem Porphyrinring verknüpft,45 um die Lipophilie und damit die Bioverfügbarkeit zu erhöhen. Dieser Komplex bindet mit so hoher Affinität an den H‐Telo‐Quadruplex, dass dessen Parallelkonformation zerstört wird.…”
Section: Verbindungen Die Mit Dna üBer π‐Stapelung Wechselwirkenunclassified
“… Einige oktaedrisch koordinierte Ruthenium(II)‐Komplexe, die über eine Kombination aus π‐Stapelung der Liganden und elektrostatischen Wechselwirkungen mit Furchen oder Schleifen an DNA‐Quadruplexe binden. a) [RuCl(phen) 2 (MPyTPP)] + 45. b) Lumineszierende Zweikernkomplexe mit aromatischen Diiminliganden44a und c) ihre einkernigen Analoga 34.…”
Section: Verbindungen Die Mit Dna üBer π‐Stapelung Wechselwirkenunclassified
“…Recently, evidence has shown that ruthenium (II) complexes can also act as potential intercalators of G-quadruplex [11,12]. For example, ruthenium complex with polypridine has high affinity with G-quadruplex [13].…”
Section: Synthesis and Characterization Of Chiral Ruthenium(ii) Complmentioning
confidence: 99%
“…The concentrations of Cu(2,3-tmtppa), Cu (3,4-tmtppa) and Cu(PcTs) was determined using molar extinction coefficient values of 1. [14]. To determine the quenching constant, Stern-Volmer equation (2) and its modified form (3) was applied [15].…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%